4D in situ synchrotron X-ray tomographic microscopy and laser-based heating study of oil shale pyrolysis. (1st February 2019) - Saif, Tarik; Lin, Qingyang; Gao, Ying; Al-Khulaifi, Yousef; Marone, Federica; Hollis, David; Blunt, Martin J.; Bijeljic, Branko
Highlights: Green River oil shale pyrolysis was characterized using 4-D synchrotron imaging. Laser-based heating was combined with X-ray synchrotron imaging at the micron-scale. Digital Volume Correlation was used to generate 3-D full-field strain maps. First micro-fractures were observed at 354 °C followed by rapid pore space expansion. Fracture development in oil shale depends on the dynamics of the local strain field. Abstract: The comprehensive characterization and analysis of the evolution of micro-fracture networks in oil shales during pyrolysis is important to understand the complex petrophysical changes during hydrocarbon recovery. We used time-resolved X-ray microtomography to perform pore-scale dynamic imaging with a synchrotron light source to capture in 4-D (three-dimensional image + real time) the evolution of fracture initiation, growth, coalescence and closure. A laser-based heating system was used to pyrolyze a sample of Eocene Green River (Mahogany Zone) up to 600 °C with tomograms acquired every 30 s at 1.63 µm computed voxel size and analyzed using Digital Volume Correlation (DVC) for full 3-D strain and deformation maps. At 354 °C the first isolated micro-fractures were observed and by 378 °C, a connected fracture network was formed as the solid organic matter was transformed into volatile hydrocarbon components. With increasing temperature, we observed simultaneous pore space growth and coalescence as well as temporary closure of minor fractures caused by local compressive stresses. This indicates that the evolution of individual fractures not only depends on organic matter composition but also on the dynamic development of neighboring fractures. Our results demonstrate that combining synchrotron X-ray tomography, laser-based heating and DVC provides a powerful methodology for characterizing dynamics of multi-scale physical changes during oil shale pyrolysis to help optimize hydrocarbon recovery.